2003
DOI: 10.1074/jbc.m210250200
|View full text |Cite
|
Sign up to set email alerts
|

NFATc1 Mediates Vascular Endothelial Growth Factor-induced Proliferation of Human Pulmonary Valve Endothelial Cells

Abstract: Mice deficient for the transcription factor NFATc1 fail to form pulmonary and aortic valves, a defect reminiscent of some types of congenital human heart disease. We examined the mechanisms by which NFATc1 is activated and translocated to the nucleus in human pulmonary valve endothelial cells to gain a better understanding of its potential role(s) in post-natal valvular repair as well as valve development. Herein we demonstrate that activation of NFATc1 in human pulmonary valve endothelial cells is specific to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 38 publications
4
92
1
Order By: Relevance
“…In summary, based on results presented here, as well as previous studies (Dor et al, 2001;Johnson et al, 2003), we speculate that by inducing nuclear translocation of NFATc1, zebrafish VEGF-R(s) regulate genes involved in proliferation, migration, and differentiation of endocardial cells in the valveforming region of the developing heart valve in a precisely regulated spatiotemporal manner. This speculation is consistent with recent findings reported by Chang and colleagues (Chang et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In summary, based on results presented here, as well as previous studies (Dor et al, 2001;Johnson et al, 2003), we speculate that by inducing nuclear translocation of NFATc1, zebrafish VEGF-R(s) regulate genes involved in proliferation, migration, and differentiation of endocardial cells in the valveforming region of the developing heart valve in a precisely regulated spatiotemporal manner. This speculation is consistent with recent findings reported by Chang and colleagues (Chang et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…The role of VEGF in EMT is likely to be complex, and depend on spatial and temporal regulation given that, in two other studies of mouse embryonic valve development, VEGF was found to be a positive regulator of EMT (Enciso et al, 2003;Hallaq et al, 2004). In our laboratory, we showed a functional link between VEGF and the transcription factor NFATc1 in human post-natal valve endothelial cells (HPVEC) (Johnson et al, 2003). This prompted us to test directly the role of VEGF-R in cardiac valve development.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…2B). This indicates that VEGFR2 is dispensable for Sema6D signaling during this stage of cardiac development, and rather suggests that the Plexin-A1-VEGFR2 complex may mediate the Sema6D activity at the later stage, particularly in endocardiac cushion formation, in which VEGF is known to be critically involved (Dor et al 2001;Johnson et al 2003).…”
Section: Genes and Development 443mentioning
confidence: 99%